DESCRIPTION OF BLOOD HEMOGLOBIN LEVELS IN VAPE USERS IN THE HEXOHM COMMUNITY BENGKULU CITY IN 2021 - Tedy Febriyanto; Guntur Baruara; Rezu Ardhiana (Poltekkes Kemenkes Bengkulu, 2022)
E-cigarettes are a new trend in Indonesian society, especially young people, not only men but also women who are fans of this electric cigarette which can be called a vape or vapor, this electric cigarette uses liquid (liquid) as a substitute for tobacco . Then this liquid turns into thick smoke. It is known that in the liquid vape content there is diacetyl which is an additive that is usually used in the production of foods such as popcorn, caramel and butter that can cause addiction. Diacetyl which is added to the liquid causes serious inflammation, which results in the lungs not having a place to exchange oxygen with CO, causing shortness of breath and difficulty breathing deeply, thus making hemoglobin levels increase because the body cannot supply enough oxygen. This happens because when smoking hemoglobin instead of taking the oxygen the body needs but instead binds to carbon monoxide .The type of research used in this study is descriptive research, namely research conducted to describe blood hemoglobin levels in electronic cigarette users in the Hexohm community of Bengkulu city in 2021. It is known that from the 40 respondents studied, almost most of them have normal hemoglobin levels and most have abnormal hemoglobin levels. Normal hemoglobin level is 12-15 g/dl. Based on the results of the examination of Hemoglobin in vape users in the Hexohm community levels in Bengkulu City, it showed that the respondents in the higher category were 22 respondents, and in the almost normal category 18 respondents. Suggestions for other researchers so that it can be used as a reference that will later be useful for further research. And it is hoped that further research will be better.